LEGAL RESPONSIBILITIES OF PT. INSURANCE OF INDONESIAN SERVICES IN COMPLETION OF CLAIM INSURANCE OF TRANSPORTATION OF GOODS IN SEA - Tri Mulyatno Budhi Hartanto (International Journal of Law and Legal Ethics, 2020)
Transportation by sea must be based on consideration, both in economic terms and in terms of security or safety. Ships are able to transport goods in relatively large quantities compared to using transportation by land or air, especially if the goods have the property not easily damaged or rotten. The importance of protection for assets or wealth, both personal and corporate property, encourages many people or companies to look at the insurance industry as a way to anticipate losses suffered by the community and entrepreneurs. The development of existing problems and emerging now, so many insurance companies that offer a variety of different types of profit products, the benefits derived from insurance products lead to different risk coverage. The process of settling insurance claims for the transport of goods at sea by PT. Asuransi Jasa Indonesia, namely: the insured claims report, claim research, initial loss report, preliminary survey, preliminary analysis, temporary loss report, independent surveyor / loss adjuster / average adjuster, claim support documents, claim submission to headquarters, claim decision, report claim settlement, claim recovery. The form of responsibility given by PT. Asuransi Jasa Indonesia in settling insurance claims for the carriage of goods at sea is to provide compensation to the insured in accordance with the agreement that has been reached between the insured and the guarantor, namely PT. Insurance Services Indonesia. The conditions of coverage used by PT. Asuransi Jasa Indonesia for the settlement of sea freight insurance claims using Lloyd's standard conditions, the Institute Cargo Clauses. Lloyd's standard conditions, namely: Full Cover or Institute Cargo Clauses A (ICC. A 1/1/82), Restriced Full Cover or Institute Cargo Clauses B (ICC. B 1/1 82), Stranding Cover or Institute Cargo Clauses C (ICC. A ICC C 1/1/82). Generally from the three Lloyd's standard conditions above, PT. Asuransi Jasa Indonesia uses or uses the Full Coverage condition or Institute Cargo Clauses A (ICC. A 1/1/82)